2017
DOI: 10.1039/c6nr08892a
|View full text |Cite
|
Sign up to set email alerts
|

Color-stable water-dispersed cesium lead halide perovskite nanocrystals

Abstract: Cesium lead halide perovskite nanocrystals are being lately explored for optoelectronic applications due to their emission tunability, high photoluminescence quantum yields, and narrow emission bands. Nevertheless, their incompatibility with polar solvents and composition homogenization driven by a fast anion-exchange are still important drawbacks to overcome. Herein we report on a successful encapsulation of colloidal perovskite nanocrystals within solid-lipid structures mainly consisting of stearic acid. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 51 publications
1
89
0
Order By: Relevance
“…More recently, Gomez et al 67. reported the application of solid lipid structures to encapsulate CsPbBr 3 NCs that were stable up to 2 months in water, albeit at a low PLQY (around 11%) likely due to initial water degradation.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Gomez et al 67. reported the application of solid lipid structures to encapsulate CsPbBr 3 NCs that were stable up to 2 months in water, albeit at a low PLQY (around 11%) likely due to initial water degradation.…”
Section: Discussionmentioning
confidence: 99%
“…[64,86] They also tend to degrade under exposure to high temperature [52] or high-energy electron beams. To overcome these obstacles, several groups explored several solutions, such as encapsulation strategy [137,138] and surface coating method. To overcome these obstacles, several groups explored several solutions, such as encapsulation strategy [137,138] and surface coating method.…”
Section: Stability Issuesmentioning
confidence: 99%
“…To overcome these obstacles, several groups explored several solutions, such as encapsulation strategy [137,138] and surface coating method. [137,138] In the former case, it was found that the PL QY of the perovskite−polymer nanocomposite films undergoes no change under continuous water-soaking for >4 months. [137,138] In the former case, it was found that the PL QY of the perovskite−polymer nanocomposite films undergoes no change under continuous water-soaking for >4 months.…”
Section: Stability Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,7,[23][24][25] We choose the MAPbBr 3 -NCs as the reference sample due to the synthesis conditions are relatively mature, and the MPACs www.advmat.de www.advancedsciencenews.com (up to five-photon) of MAPbBr 3 NCs have been investigated. [31] To get more insights into the enhancement of nonlinear optical performance of ZJU-28⊃MAPbBr 3 , time-resolved PL measurements using single-photon (436 nm) and multiphoton (for example, 2PE (960 nm), 3PE (1440 nm), 4PE (1800 nm) and 5PE (2100 nm)) excitation of MAPbBr 3 NCs and ZJU-28⊃MAPbBr 3 were performed ( Figure S11, Supporting Information). We have previously characterized that the synthesized MAPbBr 3 -NCs size is about 9 nm and the PLQY is 87.9%, which are basically consistent with the reported data.…”
Section: Multiphoton Excitationmentioning
confidence: 99%